Toleration and other essays - Voltaire, 1694-1778; McCabe, Joseph, 1867-1955 (Salt Lake City, UT : Project Gutenberg, 2021)
"Toleration and Other Essays" by Voltaire is a collection of philosophical essays written in the 18th century. The anthology revolves around themes of religious tolerance, critique of dogma, and the reflections on the contemporary social and political context surrounding Voltaire's life. Each essay serves as a potent discourse against intolerance and a call for the liberty of thought, showcasing Voltaire's role as a significant figure in advancing human rights and rationalism. The opening portion of the book begins with an introduction that contextualizes Voltaire$1 (Bs work and influence on modern thought. It recounts the historical significance of his contributions to the concept of toleration, particularly in relation to the wrongful execution of Jean Calas, a Protestant falsely accused of murdering his son. This incident serves as a critical case study of the repercussions of fanaticism and judicial error, emphasizing Voltaire's profound humanitarian perspective as he sheds light on the injustices prevalent in his time. Through the narrative of Calas' trial and execution, Voltaire illustrates the destructive effects of religious intolerance and advocates for a more compassionate and rational approach to societal governance. (This is an automatically generated summary.)s
Introduction -- In connection with the death of Jean Calas -- On superstitution -- On the interpretation of the Old Testament -- On the interpretation of the New Testament -- Epistle to the Romans -- The sermon of the fifty -- The questions of Zapata -- We must take sides; or, the principal of action -- Poem on the Lisbon disaster.
Release date is 2021-03-18
Turgut Dincer, Susan Carr and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Christianity -- Controversial literature; Rationalism; Toleration -- Early works to 1800; Bible -- Controversial literature; Religion -- Controversial literature